Performance analysis of Linux containers for high performance computing applications. (2017) - Beserra, David; Moreno, Edward David; Endo, Patricia Takako; Barreto, Jymmy; Fernandes, Stênio; Sadok, Djamel
Although cloud infrastructures can be used as High Performance Computing (HPC) platforms, many issues from virtualisation overhead have kept them almost unrelated. However, with advent of container-based virtualisation, this scenario acquires new perspectives because this technique promises to decrease the virtualisation overhead, achieving a near-native performance. In this work, we analyse the performance of a container-based virtualisation solution - Linux Container (LXC) - against a hypervisor-based virtualisation solution - KVM - under HPC activities. For our experiments, we consider CPU and (network and inter-process) communication performance. Results show that hypervisor type can impact distinctly in performance according to resource used by HPC application.